Paediatric thyroid surgery is safe – experiences at a tertiary surgical centre (Swiss Medical Weekly, 2014)
PRINCIPLES: Thyroidectomy in children is rare and mostly performed because of thyroid neoplasms. The aim of this study based on prospective data acquisition was to evaluate whether thyroid surgery in children can be performed as safely as in adults when undertaken by a team of adult endocrine surgeons and paediatric surgeons. METHODS: Between 2002 and 2012, 36 patients younger than 18 years underwent surgery for thyroid gland pathologies. All surgical procedures were performed by an experienced endocrine surgeon and a paediatric surgeon. Baseline demographic data, surgical procedure, duration of operation, length of hospital stay, and postoperative morbidity and mortality were analysed. RESULTS: The median age of all patients was 13 years (range 2–17 years), with predominantly female gender (n = 30, 83%). The majority of operations were performed because of benign thyroid disease (n = 27, 75%) and only a minority because of malignancy or genetic abnormality with predisposition for malignant transformation (MEN) (n = 9, 25%). Total thyroidectomy was performed in the majority of the patients (n = 24, 67%). The median duration of the surgical procedure was 153 minutes (range 90–310 minutes). The median hospital stay was 5 days (3‒11 days). One patient developed persistent hypoparathyroidism after neck dissection due to cancer. One persistent and two temporary recurrent nerve palsies occurred. CONCLUSION: This study demonstrated that paediatric thyroidectomy is safe as performed by this team of endocrine and paediatric surgeons, with acceptable morbidity even when total thyroidectomy was performed in the case of benign disease.